Initial German experience with transapical implantation of a second-generation transcatheter heart valve for the treatment of aortic regurgitation - Seiffert, Moritz; Bader, Ralf; Kappert, Utz; Rastan, Ardawan; Krapf, Stephan; Bleiziffer, Sabine; Hofmann, Steffen; Kallenbach, Klaus; Conradi, Lenard; Schlingloff, Friederike; Wilbring, Manuel; Schafer, Ulrich; et al. (Jacc-Cardiovascular Interventions, 2014)
This analysis reports on the initial German multicenter experience with the JenaValve (JenaValve Technology GmbH, Munich, Germany) transcatheter heart valve for the treatment of pure aortic regurgitation.Experience with transcatheter aortic valve implantation (TAVI) for severe aortic regurgitation is limited due to the risk of insufficient anchoring of the valve stent within the noncalcified aortic annulus.Transapical TAVI with a JenaValve for the treatment of severe aortic regurgitation was performed in 31 patients (age 73.8 ± 9.1 years) in 9 German centers. All patients were considered high risk for surgery (logistic EuroSCORE [European System for Cardiac Operative Risk Evaluation] 23.6 ± 14.5%) according to a local heart team consensus. Procedural results and clinical outcomes up to 6 months were analyzed.Implantation was successful in 30 of 31 cases (aortic annulus diameter 24.7 ± 1.5 mm); transcatheter heart valve dislodgement necessitated valve-in-valve implantation in 1 patient. Post-procedural aortic regurgitation was none/trace in 28 of 31 and mild in 3 of 31 patients. During follow-up, 2 patients underwent valvular reinterventions (surgical aortic valve replacement for endocarditis, valve-in-valve implantation for increasing paravalvular regurgitation). All-cause mortality was 12.9% and 19.3% at 30 days and 6 months, respectively. In the remaining patients, a significant improvement in New York Heart Association class was observed and persisted up to 6 months after TAVI.Aortic regurgitation remains a challenging pathology for TAVI. After initial demonstration of feasibility, this multicenter study revealed the JenaValve transcatheter heart valve as a reasonable option in this subset of patients. However, a significant early noncardiac mortality related to the high-risk population emphasizes the need for careful patient selection.
EVALuna2:12061